2014
DOI: 10.4067/s0370-41062014000400006
|View full text |Cite
|
Sign up to set email alerts
|

Reparación toracoscópica de atresia esofágica con y sin fistula traqueoesofágica

Abstract: Rev chil pediatr 2014; 85 (4): 443-447Recibido el 21 de marzo de 2013, última versión aceptada para publicación el 18 de febrero de 2014. Potenciales conflictos de interés:Este trabajo cumple con los requisitos sobre consentimiento /asentimiento informado, comité de ética, financiamiento, estudios animales y sobre la ausencia de conflictos de intereses según corresponda. of them with type III EA, 4 with type I and one unclassifiable, were part of the study. 13 patients underwent ligation, cut of tracheoesophag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
(23 reference statements)
0
5
0
1
Order By: Relevance
“…Thoracoscopic Approach to Delayed/staged Repairs 5,10,26,[35][36][37][38][39][40][41] In the 2 decades between 1999 and 2019, a total of 10 articles describing thoracoscopic staged repairs were identified and offered 73 neonates for this analysis (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thoracoscopic Approach to Delayed/staged Repairs 5,10,26,[35][36][37][38][39][40][41] In the 2 decades between 1999 and 2019, a total of 10 articles describing thoracoscopic staged repairs were identified and offered 73 neonates for this analysis (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…8 During the last 10 years, thoracoscopic repair of EA/TEF has become a standard procedure in many pediatric surgical centers, which was evident from a recent survey that showed that 46% preference for the thoracoscopic approach. 10,15 Outcomes of thoracoscopic approach have been reported to be comparable to open surgery. 22 More recently, this has also been confirmed in a meta-analysis comparing thoracoscopy with thoracotomy, which showed no significant differences between the approaches; with the exception of operative time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Além disso, análise de dados de 2015 da América Latina, observou-se que entre os diagnósticos efetuados durante a vida pós-neonatal, é possível perceber uma relação direta da AE com duas variáveis: idade gestacional e sexo masculino 8,9 . O tratamento da patologia é unicamente cirúrgico 10 .…”
Section: Introductionunclassified